Bridging the Printed or Digital Controversy: A Meta-Analysis of the Impact of Digital and Print Resources on College Students’ Reading Comprehension - de-la-Peña, Cristina; Chaves-Yuste, Beatriz; Luque-Rojas, María Jesús (Journal of College Reading and Learning, 2024)
Recent studies have shown contradictory results on the influence of digital technology on the level of reading comprehension performance in college students. This paper examines the existence of differences in reading comprehension between the use of digital technology and traditional support in college students. A meta-analysis of international publications between 2012–2022 is carried out with a total sample of 481 students. The results indicate that technology has not an average positive effect on reading comprehension. The study evidences improvement in students’ reading comprehension with printed medium with an effect size of 0.19. The practical implications should be aimed at stimulating research with new digital resources and increasing educational actions on teaching methodology in the classroom.
Keywords: digital technology; meta-analysis; reading comprehension; college students